ESTUDO RESTROSPECTIVO EM BIOPSIAS HEPATICAS, DO ANTIGENO DE SUPERFICIE DO VIRUS DA HEPATITE B, PELOS METODOS DE ORCEINA E DE IMUNOFLUORESCENCIA INDIRETA - Caldas, M. L.R.; Maffei, H. V.L.; Rezende, T. A. (My University, 1979)
A retrospective study of the HBsAg was done in 56 liver biopsies of children less than 12 year old and 78 biopsies of adults. The study was performed by orcein stain and indirect immunofluorescence (IIF). In 23 of the adult patients, the serological detection of HBsAg and antibodies (HBsAb) was determined by reverse passive haemagglutination technique. The adult patients' histological diagnoses were variable and included acute or chronic hepatitis (20.5%) and cirrhosis (24.4%). Orcein was positive in 7 and IIF in 6 cases; 5 biopsies were positive by both methods. The highest incidence of HBsAg was seen in active cirrhosis (75%), including two cases of alcoholic cirrhosis. In the 23 serologically studied patients, 15 cases were HBsAg negative and 3 were HBsAg positive both in the liver and serum; only 2 cases showed discrepancy between these results. Three patients were HBsAb positive and HBsAg negative both in the liver and serum. All children's biopsies were HBsAg negative. Among these patients, 26.8% had acute or chronic hepatitis and 10.7% cirrhosis. Serological and tissue techniques for HBsAg and HBsAb detection have different sensitivity. This should be kept in mind when studying the incidence of hepatitis B virus related to liver diseases.
A retrospective study of hepatitis B surface antigen (HBsAg) in liver biopsies by means of orcein stain and indirect immunofluorescent method